New species of Pteromalidae and Torymidae (Hymenoptera: Chalcidoidea) from California, with taxonomic notes - Burks, R. A.; Redak, R. A. (Zootaxa, 2004)
Two new species of Pteromalinae, and a new species of the torymid genus Pseuderimerus are described from Californian and Mexican material. Additional notes are provided concerning the identification of the genera involved. Chlorocytus analis is transferred from Pteromalus (Habrocy- tus) and redescribed, with discussion of the accuracy of its published host record. New taxa: Meximalus skinnerensis n. sp., Euteloida basalis n. sp., Pseuderimerus burgeri n. sp.